2020
DOI: 10.1177/0003134820947391
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative Usage of Dexamethasone in Diabetic Patients Undergoing Total Hip or Knee Arthroplasty for Control of Nausea and Vomiting

Abstract: Background Dexamethasone has been used in surgical patients to decrease nausea, vomiting, and postoperative pain. However, it is not well studied how much dexamethasone complicates glucose control in diabetic patients and whether this leads to poor surgical outcomes. Methods We analyzed 256 diabetic patients who underwent elective hip and knee arthroplasty and evaluated the groups that received dexamethasone intraoperatively (201 patients), those who received dexamethasone postoperatively (237 patients), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In concurrence with O'Connell et al ( 2018) and Wasfie et al (2021), these findings add support to the conflicting body of literature that dexamethasone does cause increased blood glucose levels in diabetic patients undergoing TJA. These findings also support the existing consensus in the literature that dexamethasone administration is not associated with increased incidence of PJIs in the general TJA population or in the diabetic patient population (Allen et al, 2020;Godshaw et al, 2019;Klement et al, 2018;O'Connell et al, 2018;Richardson et al, 2016;Wasfie et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In concurrence with O'Connell et al ( 2018) and Wasfie et al (2021), these findings add support to the conflicting body of literature that dexamethasone does cause increased blood glucose levels in diabetic patients undergoing TJA. These findings also support the existing consensus in the literature that dexamethasone administration is not associated with increased incidence of PJIs in the general TJA population or in the diabetic patient population (Allen et al, 2020;Godshaw et al, 2019;Klement et al, 2018;O'Connell et al, 2018;Richardson et al, 2016;Wasfie et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…There have been differing reports regarding whether perioperative dexamethasone use in diabetic patients undergoing TJA causes significant postoperative hyperglycemia. Two studies found that patients have increased hyperglycemia postoperatively but with no link to clinical significance (O'Connell et al, 2018; Wasfie et al, 2021). In contrast, two studies found that dexamethasone did not increase postoperative hyperglycemia (Allen et al, 2020; Godshaw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for exclusion after full-text examination are shown in Appendix II. These reasons include no control group with diabetes, 36–39 exclusion of participants with diabetes, 40–42 inclusion of participants with impaired glucose tolerance but no formal diagnosis of diabetes mellitus, 43 administration of multiple dexamethasone doses, 23 use of oral dexamethasone, 44 report of average rather than maximal blood glucose level, 45 failure to report quantitative blood glucose, 46 and grouping of participants with and without diabetes in a single data set 47 …”
Section: Resultsmentioning
confidence: 99%
“…These reasons include no control group with diabetes, [36][37][38][39] exclusion of participants with diabetes, [40][41][42] inclusion of participants with impaired glucose tolerance but no formal diagnosis of diabetes mellitus, 43 administration of multiple dexamethasone doses, 23 use of oral dexamethasone, 44 report of average rather than maximal blood glucose level, 45 failure to report quantitative blood glucose, 46 and grouping of participants with and without diabetes in a single data set. 47 Eleven studies were critically appraised and underwent data extraction and synthesis (Figure 1). Ten studies were ultimately included in the meta-analysis.…”
Section: Study Inclusionmentioning
confidence: 99%
“…We were particularly interested in the article by Wasfie TJ et al 1 that evaluated the preoperative use of dexamethasone in diabetic patients undergoing total hip or knee arthroplasty for control of nausea and vomiting. They conclude that, when compared to other antiemetics, dexamethasone had no discernible effect on postoperative nausea and vomiting in diabetic patients having elective total knee and hip arthroplasty.…”
mentioning
confidence: 99%